The Role of Family Socialization in Preventing Violence in High School Student's Love Relationships in South Sulawesi - Torro, Supriadi; Darmayanti, Dyan Paramitha; Sunra, La; Rahmi R, Nurazizah (Universitas Tanjungpura, 2025)
This study aims to determine the effect of the family socialization function on preventing dating violence among high school students in South Sulawesi. A quantitative approach was used, collecting data through questionnaires from 208 high school students in South Sulawesi. The sampling technique employed was random sampling. Data analysis was conducted using simple linear regression, t-test, and coefficient of determination. The results showed that the family socialization function significantly prevented dating violence. The coefficient of determination of 0.895 indicates that the socialization function accounts for 89.5% of the variation in dating violence prevention. This study provides important implications for stakeholders, including schools, families, and local governments, to develop targeted strategies for preventing dating violence. The findings highlight the crucial role of adequate family socialization in shaping healthy, non-violent relationships among adolescents. Future research could explore specific socialization strategies and their long-term impacts on relationship dynamics and violence prevention in diverse cultural contexts.